National Action plan for Agriculture GHG Inventory Improvement: Suriname - Stevens, Luanne (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The CARICOM AgREADY project, funded by the Green Climate Fund, aims to improve the enabling conditions for climate action in the agricultural sector in nine Caribbean countries. The objectives of the project include strengthening policies, capacities, frameworks, and institutional arrangements for collecting, monitoring, measuring, reporting, verifying, and analyzing agricultural data, identifying evidenced-based and bankable projects, and disseminating best practices for institutional capacity building. In Suriname, the initiative aims to improve the agriculture greenhouse gas inventory by assessing its status, identifying areas for improvement, developing and prioritizing actions. The methodology involves reviewing inventory reports, discussing with national experts, and synthesizing results to improve institutional arrangements, data sources, collection and quality control.